2015
DOI: 10.1097/jto.0000000000000486
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Spread through Air Spaces is an Important Pattern of Invasion and Impacts the Frequency and Location of Recurrences after Limited Resection for Small Stage I Lung Adenocarcinomas

Abstract: Introduction Tumor invasion in lung adenocarcinoma is defined as infiltration of stroma, blood vessels, or pleura. Based on observation of tumor spread through air spaces (STAS), we considered whether this could represent new patterns of invasion and investigated whether it correlated with locoregional versus distant recurrence according to limited resection versus lobectomy. Methods We reviewed resected small (≤2 cm) stage I lung adenocarcinomas (n=411; 1995–2006). Tumor STAS was defined as tumor cells—micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
620
7
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(667 citation statements)
references
References 36 publications
35
620
7
5
Order By: Relevance
“…Most probably, with the latter histological diagnoses a lobectomy is still the most appropriate treatment to obtain good long-term results. A newly recognized pattern is spread through air spaces (STAS) where tumor deposits are present in lung parenchyma around the primary tumor without direct connection (8). As can be expected, a higher rate of recurrences has been described with this particular growth pattern (8).…”
Section: Editorialmentioning
confidence: 83%
“…Most probably, with the latter histological diagnoses a lobectomy is still the most appropriate treatment to obtain good long-term results. A newly recognized pattern is spread through air spaces (STAS) where tumor deposits are present in lung parenchyma around the primary tumor without direct connection (8). As can be expected, a higher rate of recurrences has been described with this particular growth pattern (8).…”
Section: Editorialmentioning
confidence: 83%
“…The authors also raise the possibility that in patients with small percentages of micropapillary tumor (5%) who do poorly may progress because of "micropapillary STAS". Of potential treatment significance, patients with STAS had a poorer prognosis only when they underwent limited resection, but not in those who underwent lobectomy, suggesting a role for lobectomy even in small lesions (39).…”
Section: Issues With Current Histologic Classification Systemmentioning
confidence: 99%
“…Although several studies found presence of STAS to be a worse prognostic factor, its influence in staging was unknown. Dai et al (6) showed that patients with stage I adenocarcinoma <2-3 cm and the presence of STAS, which was based on the definition by Kadota et al (2), had prognosis similar to that of patients with stage IB adenocarcinoma; therefore, STAS may possibly change the pathologic stage of a tumor. The concept of STAS has also been applied to squamous cell carcinoma of the lung.…”
mentioning
confidence: 99%
“…Interestingly, the connection of a tumor island to the main tumor was demonstrated by three-dimensional reconstruction analysis. Kadota et al (2) reported that tumor spread through air spaces (STAS), defined as the presence of tumor cells that goes beyond the edge of the main tumor to within at least the first alveolar layer in the lung parenchyma, was a significant risk factor for recurrence of small (≤2 cm) lung adenocarcinoma in patients who underwent limited resection. We showed that semiquantitative assessment was a useful prognostic factor in patients with small (≤2 cm) lung adenocarcinoma.…”
mentioning
confidence: 99%